A regional analysis of wage determination in Poland - Fiona Duffy; Patrick Paul Walsh (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2000)
A simple model of wage setting and restructuring predicts that the average wage level in a regional labour market in Poland, among other factors, will be negatively related to the unemployment rate and positively related to the degree of regional restructuring. As in Blanchflower and Oswald (1994), the estimated unemployment elasticity of pay across regions is approximately - 0.1. Workers in low unemployment regions earn more pay indicating the presence of profit sharing. Workers in more restructured regions are shown to receive higher premiums in pay indicating compensation for exposure to risk during restructuring.
Keywords: J6; L0; O5; 330; Wage Determination; Unemployment; Restructuring and Polish Regions